Two-swarm cooperative artificial fish algorithm for bound constrained global optimization - Rocha, Ana Maria A. C. (2014)
This study presents a new two-swarm cooperative ﬁsh intelligence algorithm for solving the bound constrained global optimization problem. The master population is moved by a Lévy distribution and cooperates with the training population that follows mainly the classical ﬁsh behaviors. Some numerical experiments are reported.